2021
DOI: 10.3390/foods10050942
|View full text |Cite
|
Sign up to set email alerts
|

Bread Fortified with Cooked Purple Potato Flour and Citrus Albedo: An Evaluation of Its Compositional and Sensorial Properties

Abstract: This research aimed to explore the feasibility of fortifying bread with cooked Vitelotte potato powder and Citrus albedo, comparing the use of baker’s yeast or sourdough as leavening agents. Breads obtained were thus subjected to physico-chemical and sensory characterizations. The replacement of part of the wheat flour with purple potato and albedo determined a significant enhancement of the phenolic profile and antioxidant status of fortified breads, as well as a longer shelf life. Thanks to its acidity and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 84 publications
(109 reference statements)
1
32
0
Order By: Relevance
“…Moreover, it shows a good mineral content and lipidic profile due to its richness in mono and polyunsaturated acids (oleic, linoleic, and linolenic acid) [ 36 ]. In the literature, there are several studies that have highlighted the health benefits related to a regular and appropriate ingestion of fibre [ 37 , 38 , 39 , 40 ] and phenolic compounds [ 41 , 42 , 43 ], which are also exploited as natural additives in foods, substituting chemical ones, due to their antioxidant and antimicrobials actions [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it shows a good mineral content and lipidic profile due to its richness in mono and polyunsaturated acids (oleic, linoleic, and linolenic acid) [ 36 ]. In the literature, there are several studies that have highlighted the health benefits related to a regular and appropriate ingestion of fibre [ 37 , 38 , 39 , 40 ] and phenolic compounds [ 41 , 42 , 43 ], which are also exploited as natural additives in foods, substituting chemical ones, due to their antioxidant and antimicrobials actions [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to the authors, these findings showed that grape pomace enriched bread could promote an antioxidant environment in the digestive tract [78]. In the same regard, Taglieri et al [79] showed that secondary metabolites from Vitellote potatoes significantly improved the phenolic content and antioxidant activity of fortified bread with the highest values when sourdough was the leavening agent. The capacity of hemp flour to deliver biologically active compounds and flavors in bread was also investigated by metabolomics analyses.…”
Section: Metabolite Profiling During Wheat Dough Fermentationmentioning
confidence: 94%
“…In order to compare the nine vineyards, the program Root Data Analysis Framework based on C++ language was used for the data processing [27,28]. The program uses a minimum model that allows for the following function to be reduced to a minimum:…”
Section: Statistical Analysesmentioning
confidence: 99%